Heritabilitas Hasil Pemurnian Galur Harapan Mentimun (Cucumis sativus L.) Kecil Berwarna Hijau Sedang Generasi 4 - Asahak, Alif Ibnu Sina; Rajiman, Rajiman; Fauziah, Nicky Oktav (Jurnal Agroteknologi (Agronu), 2025)
Currently, the market demand for cucumber (Cucumis sativus L.) is high, but productivity is declining due to the limited availability of quality seeds. Therefore, a sustainable plant breeding program is necessary to produce superior, high-quality varieties. This research aims to determine the heritability and clustering of promising cucumber lines (Cucumis sativus L.) with a medium green color in the fourth generation. The study was conducted from December 2024 to February 2025 at the Teaching Factory Celeban Polbangtan Yogyakarta-Magelang in Tahunan, and Umbulharjo District, Yogyakarta City, Special Region of Yogyakarta, at coordinates 7°48'17"S, 110°22'54"E. The research method employed a single plant approach, involving the planting and observation of each cucumber plant from the promising fourth generation resulting from the crossbreeding of KE 4723 and AGB KE 0316. Quantitative observation data were analyzed using heritability, cluster, and descriptive methods, while qualitative data were collected using cluster analysis methods. Based on the research results, the heritability value for the seven quantitative characters is categorized as high, with a criterion of value ≥ 50%, indicating high effectiveness for selection. The results of the cluster analysis on the diversity of characteristics among strains 01.08, KE 4723, and AGB KE 0316, based on 9 characteristics, reveal 3 clusters: cluster 1 is characterized by light green fruit skin color, cluster 2 by medium green fruit skin color, and cluster 3 by dark green fruit skin color